Physiological and operative severity score for the enumeration of mortality and morbidity scoring systems for assessment of patient outcome and impact of surgeons' and anesthesiologists' performance in hepatopancreaticobiliary surgery - Argyro Fassoulaki; Konstantinos Chondrogiannis; Chryssoula Staikou (Saudi Journal of Anaesthesia, 2017)
Context: The physiological and operative severity score for the enumeration of mortality and morbidity (POSSUM) is a scoring system used to predict morbidity and mortality. Aims: We compared the physiological and operative risk, the expected morbidity and mortality, and the observed postoperative mortality among patients operated by different surgeons and anesthetized by different anesthesiologists. Settings and Design: This was a retrospective, single center study. Subjects and Methods: The anesthetic records of 159 patients who underwent hepatopancreaticobiliary surgery were analyzed for the physiological and operative severity, POSSUM morbidity, POSSUM and Portsmouth POSSUM (P-POSSUM) mortality scoring systems, observed mortality in 30-days, 3, 6, and 12 months postoperatively, duration of surgery, and units of packed red blood cells (PRBC) transfused. These variables were compared among patients operated by five different surgeons and anesthetized by seven different anesthesiologists. Statistical Analysis: One-way analysis of variance was used for normally and Kruskal–Wallis test for nonnormally distributed responses. Differences in percentages of postoperative mortality were assessed by Chi-squared test. Results: The physiological severity, POSSUM morbidity, POSSUM and P-POSSUM mortality scores, and observed mortality at 1, 3, 6, and 12 months postoperatively did not differ among patients operated by different surgeons and anesthetized by different anesthesiologists. Duration of surgery (P < 0.001), PRBC units transfused (P = 0.002), and operative severity (P = 0.001) differed significantly among patients operated by different surgeons. Conclusions: The physiological severity score, POSSUM and P-POSSUM scores did not differ among patients operated by different surgeons and anesthetized by different anesthesiologists. The different operative severity scores did not influence the observed mortality in the postoperative period.